Structure-property relationship between different molecular precursors and the final properties of carbon dots: Preparation, characterization and applications as sensors for metal ions - da Silva Pinto, Tarciane; Ferreira, Arthur Hegermann; Taborda, Nestor Cifuentes; de Mesquita, João Paulo; Fraga Freitas, Erico Tadeu; do Amparo, Sthéfany Zaida Silva; Soares, Edmar Avellar; Donnici, Claudio Luis; de Paula, Everton Luiz; Pereira, Fabiano Vargas (Optical materials, 2024)
Carbon dots (CDs) have attracted significant attention in recent years due to their interesting properties, such as photoluminescence, biocompatibility, excellent water dispersibility, as well as their potential applications in different fields. Despite these features, the complexity of their photoluminescent properties remains a subject of ongoing research and still presents unresolved questions. In this work, we investigated the preparation of various CDs from different low molecular mass starting materials containing carbon, nitrogen and/or sulfur, using hydrothermal carbonization as the preparation method. The CDs were characterized using various techniques, including TEM, FTIR, photoluminescence, UV–Vis, Raman and XPS. A detailed analysis of the initial reactions between the precursors was conducted, and our main results suggest that the optical properties of the CDs are related to fluorophores formed during the initial Michael condensation reactions between the precursors. This process produces molecular fluorescence, which plays a pivotal role in the photoluminescence properties of the nanoparticles. In addition, two of the obtained CDs were used as selective and sensitive probes for metal ions, achieving a detection limit of 0.58 μM and 0.55 μM. Finally, the findings described here can guide future works in fine-tuning the design of CDs with desired properties and different potential applications. •Carbon dots were prepared from different low molecular weight precursors.•Initial Michael condensation reactions lead to fluorophore formation.•Molecular fluorescence is important in the PL properties of the nanoparticles.•Efficient Michael condensation between carbon and nitrogen sources increases QY.•Two CDs used as selective and sensitive metal ion probes (LOD = 0.55 μM for Fe3+).